Analisis Dampak Pandemi COVID-19 Terhadap Harga Saham PT Garuda Indonesia Persero (Tbk) - Sintia Emawati Pasaribu; Sintia Elmawati Pasaribu (Jurnal Aktiva : Riset Akuntansi dan Keuangan, 2020)
The COVID-19 pandemic is called a virus that is transmitted from living things to other living things that can cause death. This virus first appeared in Wuhan in December 2019 and spread to Indonesia and was announced on March 2, 2020, this event is very influential on companies in Indonesia including PT Garuda Indonesia Tbk. From the lockdown system where the government closes all access in and out of a region or country, so that the COVID-19 pandemic has a negative impact on the share price of PT Garuda Indonesia Tbk, because this company is an Indonesian international airline which means flight transportation between regions other areas. PT Garuda Indonesia is making efforts to maintain the company's share price in the current pandemic condition, namely by optimizing operations in order to align supply with market demand through initiative steps. This study aims to analyze the impact of the COVID-19 pandemic event on PT. Garuda Indonesia Tbk by knowing the average share price of this company in the 30 days before and 30 days after the announcement of the first confirmed case of COVID-19 in Indonesia. The results of this study indicate that there is a significant decrease in the share price of PT. Garuda Indonesia in the 30 day period following the announcement of the first COVID-19 case in Indonesia compared to the 30 day period prior to the announcement.